ASSOCIATION BETWEEN THE SEVERITY OF DEPRESSION AND TYPE OF DYSPEPSIA (FUNCTIONAL AND ORGANIC) IN HAJI ADAM MALIK GENERAL HOSPITAL, MEDAN - Chairun Arrasyid, Masrul Lubis & WikaHanida Lubis (International Journal of Research Science and Management, 2019)
Introduction: Dyspepsia is syndrome of pain or discomfort in the upper abdomen. Specific discomfort includes feeling full quickly, feeling full, burning, bloating in the upper abdomen and nausea. These symptoms arise due to various factors such as smoking, alcohol, overweight and obesity, stress, anxiety, and depression. Aim: This study was conducted to determine the severity of depression in patients with functional dyspepsia and organic dyspepsia at H. Adam Malik Hospital Medan. Method: This study was an observational analytic study and was conducted with a cross sectional design. The study sample was selected with simple random sampling for patients who met the criteria, until the required number of samples was met and a sample of 52 people was obtained. Data were analyzed by Fisher’s Exact tests. Results: The study revealed a relationship between the severity of depression in patients with functional dyspepsia and organic dyspepsia in the Gastroenterology Department of the Adam Malik Hospital in Medan (p = 0,036). Conclusion: There is an association between the severity of dyspepsia and type of dyspepsia, where more severe depression is associated with functional dyspepsia compared to organic dyspepsia.